Comparison of EtView (TM) tracheoscopic ventilation tube and video-assisted fiberoptic bronchoscopy during percutaneous dilatational tracheostomy - Umutoglu, Tarik; Bakan, Mefkur; Topuz, Ufuk; YILMAZ, Sinan; YILMAZ, SİNAN; Idin, Kadir; Alver, Selcuk; Ozturk, Erdogan; SALİHOĞLU, Ziya (My University, 2017)
Fiberoptic bronchoscopy (FOB) via endotracheal tube (ETT) is the most frequent utilized technique for monitoring of percutaneous dilatational tracheostomy (PDT) procedure while maintaining mechanical ventilation. Endoscopic guidance has increased the safety of this procedure; nevertheless, the use of a bronchoscope via ETT potentially may deteriorate ventilation and lead to hypercarbia and/or hypoxia. EtView tracheoscopic ventilation tube (EtView TVT) is a standard endotracheal tube with a camera and light source embedded at the tip. The objectives of this study are to introduce EtView TVT as a monitoring tool during PDT and to compare it with video assisted FOB via ETT. We hypothesized that using EtView TVT during PDT may obtain similar visualization; also may have advantages regarding better mechanical ventilation conditions when compared with video-assisted FOB via ETT. Patients, 18-75 years of age requiring mechanical ventilation scheduled for PDT were randomly allocated into two groups for airway monitorization to guide PDT procedure either with FOB via ETT (Group FOB, n = 12) or EtView TVT (Group EtView, n = 12). After standard anesthesia protocol, alveolar recruitment maneuver was applied and all patients were mechanically ventilated at pressure-controlled ventilation mode with same pressure levels. The primary outcome variable was the reduction in arterial oxygen partial pressure (PaO2) values during the procedure. Other respiratory variables and the effectiveness (the visualization and identification of relevant airway structures) of two techniques were the secondary outcome variables. Patients in both groups were comparable with respect to demographic characteristics and initial respiratory variables. Visualization and identification of relevant airway structures in any steps of the PDT procedure were also comparable. The decrease in minute ventilation in Group FOB was higher when compared with Group EtView (51 +/- 4 % vs. 12 +/- 7.3 %, p < 0.05). The decrease in PaO2 from initial levels during (34 +/- 21 % vs. 5 +/- 7 % decrease) and after (26 +/- 27 % vs. 2.8 +/- 16 % decrease) the procedure was higher in Group FOB when compared with Group EtView (p < 0.05). Considering comparable features in monitorization and advantageous features over mechanical ventilation when compared with video bronchoscopy; EtView TVT would be a good alternative for airway monitorization during PDT especially for patients with poor pulmonary reserve.